1983
DOI: 10.1037/0096-3445.112.4.457
|View full text |Cite
|
Sign up to set email alerts
|

Can a chimpanzee make a statement?

Abstract: The field of ape language has been in turmoil since the publication of Terrace's (1979) work with. Nim, a chimpanzee. Terrace's findings regarding the linguistic competencies of apes contrasted sharply with those put forth earlier by Gardner and Gardner (1971). We discuss these and other ape-language projects and contrast the preverbal communicative skills of chimpanzees with those of human children in order to, determine the cognitive competencies that chimpanzees bring to the task of language acquisition. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(50 citation statements)
references
References 34 publications
0
50
0
Order By: Relevance
“…It has also been shown that when a chimpanzee is systematically taught the communicative skills of requesting, labeling, and comprehending, indicative referential symbol usage can then appear without further training (Savage- Rumbaugh, 1984bRumbaugh, , 1986Savage-Rumbaugh, Pate, Lawson, Smith, & Rosenbaum, 1983). With the appearance of indicative usage, apes go beyond conditioned request-oriented utterances and become able to make statements about behaviors they are going to engage in, in advance of actually emitting those behaviors.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been shown that when a chimpanzee is systematically taught the communicative skills of requesting, labeling, and comprehending, indicative referential symbol usage can then appear without further training (Savage- Rumbaugh, 1984bRumbaugh, , 1986Savage-Rumbaugh, Pate, Lawson, Smith, & Rosenbaum, 1983). With the appearance of indicative usage, apes go beyond conditioned request-oriented utterances and become able to make statements about behaviors they are going to engage in, in advance of actually emitting those behaviors.…”
mentioning
confidence: 99%
“…With the appearance of indicative usage, apes go beyond conditioned request-oriented utterances and become able to make statements about behaviors they are going to engage in, in advance of actually emitting those behaviors. The ability to use symbols to orient the attention of others to particular aspects of the environment, other than the fulfillment of immediate needs, also appears to accompany the onset of indicative communication (Savage-Rumbaugh, 1984b, 1986Savage-Rumbaugh et al, 1983).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is equally clear that all vertebrates are capable of forming formally similar associations, and it is not clear that such association-formation is all that occurs when a human learns the meaning of a word. Savage- Rumbaugh et al (1983) have brought similar arguments to bear on the results reported by, among others, Gardner and Gardner (e.g., 1978), Premack (1976), and Terrace et al (1979) but the effort by Savage- Rumbaugh et al (1983) to demonstrate "representational" as opposed to "associative" naming has itself been questioned (e.g., Ristau 1983;Sugarman 1983).…”
Section: Human Intelligencementioning
confidence: 64%
“…In conclusion, I find it implausible to assume that only humans can acquire language in the face of suggestive work to the contrary with chimps and especially the ongoing unpublished dolphin work of Herman and his colleagues (Savage- Rumbaugh et al 1983). The possiblity of a continuum of linguistic skills remains strong.…”
Section: Edmund Fantinomentioning
confidence: 99%